2016
DOI: 10.1186/s12887-016-0599-5
|View full text |Cite
|
Sign up to set email alerts
|

Tracking of overweight and obesity from early childhood to adolescence in a population-based cohort – the Tromsø Study, Fit Futures

Abstract: BackgroundObesity is a serious childhood health problem today. Studies have shown that overweight and obesity tend to be stable (track) from birth, through childhood and adolescence, to adulthood. However, existing studies are heterogeneous; there is still no consensus on the strength of the association between high birth weight or high body mass index (BMI) early in life and overweight and obesity later in life, nor on the appropriate age or target group for intervention and prevention efforts. This study aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
76
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 40 publications
12
76
1
1
Order By: Relevance
“…As expected, and consistent with previous studies, childhood BMI was predictive of adult obesity risk in the current study. Of particular interest, our study also showed that both BMI levels and rate of change (linear slope) at different age points during childhood were consistently and significantly higher in adults with obesity than in those without obesity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As expected, and consistent with previous studies, childhood BMI was predictive of adult obesity risk in the current study. Of particular interest, our study also showed that both BMI levels and rate of change (linear slope) at different age points during childhood were consistently and significantly higher in adults with obesity than in those without obesity.…”
Section: Discussionsupporting
confidence: 93%
“…Numerous studies have documented that obesity in adult life has its origins in childhood . Body mass index (BMI), the most commonly used measure to diagnose obesity, in childhood is highly correlated with BMI in later life, with correlations varying from 0.3 to 0.9, depending on the time interval and age period . In addition to absolute BMI values, rapid BMI increase is also a predictor of obesity in adult life .…”
Section: Introductionmentioning
confidence: 99%
“…Reduced everyday physical activity and increased access to energy-rich nutrients have resulted in a sedentary lifestyle and an average weight gain among youths similar to what we observe in the general population (World Health Organization [WHO], 2016). These changes are alarming because frequency of obesity in childhood often remains or increases into adolescence and adulthood (Evensen, Wilsgaard, Furberg, & Skeie, 2016). Obesity and a sedentary lifestyle are closely associated with a number of non-communicable diseases (NCDs) and psychosocial problems that are dominating the health burden in the adult population (Singh, Mulder, Twisk, Van Mechelen, & Chinapaw, 2008).…”
mentioning
confidence: 99%
“…However, children in the individual family intervention received more than standard care or wait‐list control group, which might have reduced our ability to detect between‐group differences. Observational and clinical studies have reported increasing BMI SDS in children with overweight and obesity in the absence of treatment . Significant reductions in BMI SDS in both individual family and group intervention may indicate that both interventions were beneficial, though being aware the limitations of generalising BMI SDS outcomes .…”
Section: Discussionmentioning
confidence: 94%